Primary Pleomorphic Liposarcoma of Liver: A Case Report and Review of the Literature - P. R. Thippeswamy Naik; Prem Kumar; P. Vinod Kumar (Case Reports in Hepatology)
Primary liver liposarcoma is a rare disease. The knowledge of the clinical course, management, and prognosis of primary liver liposarcoma are all limited because of its rarity. Twelve cases of primary liposarcoma of the liver have been previously reported. We present the thirteenth case, which occurred in an adult male patient. A 42-year-old male patient came to our outpatient department with complaints of pain abdomen, mass per abdomen, and weight loss. Ultrasonography showed a mass arising from the the left lobe of liver. CT abdomen showed a heterogenous enhancing mass from left lobe of liver with multiple cystic and necrotic areas compressing the stomach and spleen with no evidence of metastasis. Differential diagnosis included adenoma and primary malignancy. Exploratory laparotomy and resection were done. HPE was found to be pleomorphic liposarcoma of liver.